TINJAUAN LITERATUR: PELATIHAN PEMBELAJARAM DEEP LEARNING BERBASIS STEAM UNTUK GURU SEKOLAH DASAR - Olivia; Melva Zainil; Inggria Kharisma; Annisa Olivia Memosa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the National Curriculum requires elementary school teachers to be able to design in-depth, integrated learning based on 21st-century skills. However, most teachers still have limited understanding of the concept of deep learning and how to integrate the STEAM approach into lesson plans. This gap has encouraged the implementation of community service activities in the form of training on the development and implementation of deep learning-based STEAM instruction for elementary school teachers in Tanah Datar Regency. This activity aims to improve conceptual understanding, the ability to design integrative lesson plans (RPP), and skills in implementing innovative classroom learning. The methods used include conceptual training, workshops on developing STEAM-based lesson plans, teaching simulations, science and technology diffusion through the development of digital teaching media, and classroom implementation mentoring. Data were collected through pre- and post-assessments as well as observations of participants’ active involvement. The results showed a significant improvement in three main aspects: understanding of the deep learning concept, the ability to design integrated STEAM lesson plans, and the skills to develop collaborative learning strategies. Qualitatively, teachers produced outputs in the form of integrative lesson plans and creative teaching media using Canva and Wordwall as indicators of the program’s success. The discussion indicates that a practice-based training approach, supported by continuous mentoring and institutional support, is effective in improving teachers’ pedagogical competence. This program can serve as a model for elementary school teacher professional development in rural areas to accelerate the readiness for implementing the National Curriculum based on STEAM comprehensively. Keywords: STEAM learning, deep learning, elementary school teachers, professional development, National Curriculum.